Immune Lymphocyte Infiltrate and its Prognostic Value in Triple-Negative Breast Cancer - Huertas-Caro, Carlos Alexander; Ramirez, Mayra Alejandra; Gonzalez-Torres, Henry J.; Sanabria-Salas, María Carolina; Serrano-Gómez, Silvia J. (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) occurs more frequently in young (<50 years) non-Hispanic black (NHB) and Hispanic/Latina (H/L) women. It is considered the most aggressive subtype of breast cancer, although recently immune infiltrate has been associated with long term survival, lower risk of death and recurrence and response to neoadjuvant chemotherapy. The aim of this review was to evaluate the clinical impact of the immune infiltrate in TNBC, discussing whether its prognostic value varies across different populations. A comprehensive systematic search in databases such as PubMed and Web of Science was conducted to include papers focused on TILs in TNBC in different population groups and that were published before January 2021. TNBC patients with higher levels of TILs had longer overall survival (OS) and disease-free survival (DFS) times compared to TNBC patients with low TILs levels. Similar results were observed for CD4+, CD8+ TILs populations. On the other hand, patients with high TILs levels showed a higher rate of pathological complete response (pCR), regardless to the population group (Asian, European, American). All together these results suggest that TILs subpopulations have a prognostic role in TNBC but the underlying mechanism needs to be elucidated. Although, the prognosis value of TILs were not found different between the populations groups analyzed in the revised literature, further studies including underrepresented populations with different genetic ancestries are still necessary to conclude in this regard.